Three-dimensional porous g-C3N4 for highly efficient photocatalytic overall water splitting. (May 2019) - Chen, Xianjie; Shi, Run; Chen, Qian; Zhang, Zijian; Jiang, Wenjun; Zhu, Yongfa; Zhang, Tierui
Abstract: Herein, this work constructs a three-dimensional porous graphitic carbon nitride assembled by highly crystalline and ultrathin nanosheets (3D g-C3 N4 NS). 3D g-C3 N4 NS could directly split pure water into H2 and O2 with high evolution rate up to 101.4 and 49.1 μmol g −1 h −1 under visible light, respectively, approximately 11.8 and 5.1 times higher than bulk g-C3 N4 and g-C3 N4 NS. Besides, it achieves a notable apparent quantum yield of 1.4% at 420 nm, significantly superior to previously reported Pt/g-C3 N4 . The efficient activity of 3D g-C3 N4 NS is mainly attributed to its 3D interconnected open-framework, assembled by highly crystalline ultrathin nanosheet unit, provides a pathway for faster charge carrier transport. Moreover, benefitting from its 3D structure for preventing agglomeration of nanosheets, 3D g-C3 N4 NS is stable for more than 100 h of overall water splitting reaction. Graphical abstract: Three-dimensional porous g-C3 N4 assembled by highly crystalline and ultrathin nanosheets is successfully constructed, and could efficiently split pure water into H2 and O2 with a notable quantum yield as high as 1.4% at 420 nm. Besides, it still remains stable for more than 100 h of overall water splitting reaction.Image 1 Highlights: Three-dimensional porous g-C3 N4 nanosheets (3D U-C3 N4 NS) assembled by ultrathin nanosheets was successfully fabricated. 3D U-C3 N4 NS could directly split pure water into H2 and O2 with quite high evolution rate under visible light. 3D U-C3 N4 NS achieved a notable quantum yield of 1.4% at 420 nm, significantly superior to previously reported Pt/g-C3 N4 . 3D U-C3 N4 NS could still remain stable for more than 100 h of overall water splitting reaction.